1999
DOI: 10.1177/073953299902000405
|View full text |Cite
|
Sign up to set email alerts
|

Portrait vs. Landscape: Potential Users' Preferences for Screen Orientation

Abstract: This survey finds a strong preference for portrait or vertical screen viewing of newspapers on computers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The first follows many pre-web studies of computer-mediated communication to explore the usability (efficiency and effectiveness) of information presentation on computer screens. A group of researchers at Kent University have investigated the potential adoption of digital news formats by using experimental and/or convenience (non-probability) survey methodologies to determine whether users prefer portrait-oriented (vertical) or landscape (horizontal) display of screen documents (Schierhorn et al, 1999;Wearden, 1998;Wearden and Fidler, 2001;Wearden et al, 1999). Other researchers have addressed the issue of layers and links, such as the effect of the length of initial summaries and links to sidebars (i.e.…”
Section: Previous Approaches To Online News and Information Adoption/usementioning
confidence: 99%
See 1 more Smart Citation
“…The first follows many pre-web studies of computer-mediated communication to explore the usability (efficiency and effectiveness) of information presentation on computer screens. A group of researchers at Kent University have investigated the potential adoption of digital news formats by using experimental and/or convenience (non-probability) survey methodologies to determine whether users prefer portrait-oriented (vertical) or landscape (horizontal) display of screen documents (Schierhorn et al, 1999;Wearden, 1998;Wearden and Fidler, 2001;Wearden et al, 1999). Other researchers have addressed the issue of layers and links, such as the effect of the length of initial summaries and links to sidebars (i.e.…”
Section: Previous Approaches To Online News and Information Adoption/usementioning
confidence: 99%
“…Most empirical research so far has treated online news and information adoption as one dimension of overall internet usage patterns rather than a form of use that is of interest in its own right (see, for example, Atkin et al, 1998;Ferguson and Perse, 2000;Lin, 2001;Liu et al, 2002;Mikaki et al, 2002;Papacharissi and Rubin, 2000;Rhee and Kim, 2004;Zhou and He, 2002). Of the studies with an exclusive focus on online news and information consumption, most are from the US and mostly address the result, rather than the cause, of online news and information adoption (Chyi and Larosa, 1999;Johnson and Kaye, 1998;Kaye and Johnson, 2002;Schierhorn et al, 1999;Tewksbury and Althaus, 2000;Tewksbury et al, 2001;Vargo et al, 2000;Wearden, 1998;Wearden and Fidler, 2001;Wearden et al, 1999;Weir, 1999;Wu and Bechtel, 2002). This article is a preliminary attempt to address this situation, exploring the influences of socio-structural factors on the adoption/use of online news and information among internet users.…”
mentioning
confidence: 99%
“…Sobre portales web de información, otra investigación ha demostrado la preferencia por el visionado en pantalla vertical en ordenadores de sobremesa (Wearden, Fidler, Schierhorn y Schierhorn, 1999), y otro estudio ha explorado el papel que tiene el vídeo vertical para influir en la elaboración de noticias en la televisión local: se reconoce la oportunidad creativa de producir contenidos originales para atraer nuevas audiencias (Canella, 2018).…”
Section: Las Investigaciones Sobre El Vídeo Verticalunclassified
“…More recently, the Cannes Film Festival has teamed up with TikTok Short Films to award the best shorts between 30 and 180 seconds, shot in vertical aspect ratio. (López, 2022) Along the same lines, some studies involving informative web portals have shown a preference for vertical screen viewing on desktop computers (Wearden et al, 1999), and other research in the area of communication has explored the role of vertical video and its effect on the newsroom tasks of local television news programmes. (Canella, 2018) In Spain, the news platform Playground published an article in native video format on Facebook in 2015.…”
Section: Vertical Video On Social Mediamentioning
confidence: 99%